Clinical Features of a Chinese Sample with Self-Reported Symptoms of Pathological Dissociation. Issue 3 (27th May 2021) - Fung, Hong Wang; Chan, Chitat; Ross, Colin A.; Wang, Edward K. S.
ABSTRACT: People with pathological dissociation should receive proper clinical attention and timely support. Recent studies have shown that pathological dissociation is common in the Chinese context. However, little is known about the clinical features of Chinese people with pathological dissociation. This paper reports the first data regarding trauma histories, mental health symptoms, clinical diagnoses, service usages, stigma and psychosocial needs in a convenience sample of Chinese people who screened positive for pathological dissociation on a self-report measure (N = 72). This sample was characterized by a history of trauma and high levels of trauma-related symptoms and depression. Medication treatments were the most common interventions for them; many participants did not receive psychotherapy. We found no clinical differences between participants who had and had not received psychotherapy for post-traumatic/dissociative symptoms. This implies that many participants did not have the chance of receiving specific psychotherapy even though their trauma histories and clinical symptoms were as severe as those who were receiving specific psychotherapy. Stigma and unmet psychosocial needs were common in this sample and should receive more attention in the field. Implications for research and practice are highlighted. More dissociation-informed services are required for Chinese-speaking populations.